2017
DOI: 10.1111/cbdd.13011
|View full text |Cite
|
Sign up to set email alerts
|

Concluding the trilogy: The interaction of 2,2′‐dihydroxy‐benzophenones and their carbonyl N‐analogues with human glutathione transferase M1‐1 face to face with the P1‐1 and A1‐1 isoenzymes involved in MDR

Abstract: A series of 2,2'-dihydroxybenzophenones and their carbonyl N-analogues were studied as potential inhibitors against human glutathione transferase M1-1 (hGSTM1-1) purified from recombinant E. coli. Their screening revealed an inhibition against hGSTM1-1 within a range of 0-42% (25 μM). The IC values for the two stronger ones, 16 and 13, were 53.5 ± 5.6 μΜ and 28.5 ± 2.5 μΜ, respectively. The results were compared with earlier ones for isoenzymes hGSTP1-1 and hGSTA1-1 involved in MDR. All but one bind more stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
(52 reference statements)
2
18
0
Order By: Relevance
“…Further studies on 2,2 0 -dihydroxybenzophenones showed that benzophenone 49 (Figure 5) inhibited hGSTA1-1 (IC 50 ¼ 1.77 mM) but was a weak inhibitor of hGSTP1A-1A (Pouliou et al 2015). Both benzophenones 48 and 49 are weak inhibitors of GSTP1-1, although analog 48 (Figure 5) inhibits GSTM1-1 (K i ¼ 22.3 mM) (Georgakis et al 2017). Xanthone 50 (Figure 5) inhibits hGSTA1-1 in colon cancer cell lysates and is weakly cytotoxic in Caco-2 cells (Zoi et al 2013).…”
Section: Tissue and Species Distributionmentioning
confidence: 97%
“…Further studies on 2,2 0 -dihydroxybenzophenones showed that benzophenone 49 (Figure 5) inhibited hGSTA1-1 (IC 50 ¼ 1.77 mM) but was a weak inhibitor of hGSTP1A-1A (Pouliou et al 2015). Both benzophenones 48 and 49 are weak inhibitors of GSTP1-1, although analog 48 (Figure 5) inhibits GSTM1-1 (K i ¼ 22.3 mM) (Georgakis et al 2017). Xanthone 50 (Figure 5) inhibits hGSTA1-1 in colon cancer cell lysates and is weakly cytotoxic in Caco-2 cells (Zoi et al 2013).…”
Section: Tissue and Species Distributionmentioning
confidence: 97%
“…The IC50 value for fisetin was determined as 1.2 ± 0.1 μΜ. Fisetin appears to be a strong inhibitor for hGSTA1-1, compared to other synthetic or natural inhibitors that have been studied over the last years [18][19][20][21]23,32,33]. For example, the IC50 values for colchicine [23] or synthetic 2-(pyrrolesulfonylmethyl)-N-arylimines, benzophenones and their carbonyl N-analog ranged between 22 and 71 μΜ [32,33].…”
Section: The Inhibition Of Recombinant Hgsta1-1 By Fisetinmentioning
confidence: 99%
“…Several potent inhibitors have been developed over the last years, which are classified into two groups: those that bind to the G-site and those that bind to the H-site. Numerous compounds, natural or synthetic, with different degrees of efficacy and inhibition potency, have been reported [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The phototoxicity of this class of bioactive natural products is a probable adverse effect that may limit the widespread utilization of this pharmacophore in drug design [23]. Some research groups [24][25][26][27] nonetheless continue to explore BP groups in their drug discovery efforts, and the interested reader may consult a recent review [28] for further insight into the medicinal properties of BP-containing natural products. The use of BPs in PL techniques, including their design and utility in biological investigations, is discussed in Section 3.…”
Section: Benzophenonesmentioning
confidence: 99%